Legal regulation of cyber warfare: reviewing the contribution of the Tallinn manual to the advancement of international law - Sang, Michael (Department of Public Law, 2015)
The development of modern technology is inevitably bound to change the conduct of warfare. It is also self-evident that the mode, typology and participants in current armed conflicts do not fit within the structures of traditional international law on the use of armed force. Indeed, in some cases the new conflicts pose intractable challenges to the existing law. This is particularly true with regard to the military use of cyber operations either in the context of armed self-defence or in the conduct of hostilities in time of armed conflict. The establishment of the worldwide computer network and the increasing reliance on digital services has brought about a new type of clear and present danger: the threat of cyber attack. The fact that cyber operations are a relatively novel phenomenon in the history of international law automatically raises some important questions regarding whether the existing rules of international law apply to them.6 Consider the evidence indicating that there have been Chinese government-backed cyber operations, including espionage, targeting State and corporate computer networks in the United States. The question that arises in regard to cyber incidents, like the one illustrated above, is whether international law governs them, and if so which specific rules apply, and the circumstances in which they apply. With the aim of clarifying the uncertainty as to the specific rules pertinent to cyber warfare, the Tallinn Manual on the International Law Applicable to Cyber Warfare was developed by a group of twenty renowned international law scholars and practitioners. It provides a useful basis on which to identify how and evaluate the extent to which international law applies to cyber operations. This research seeks to critically appraise both the current and prospective contribution of the Tallinn Manual to the advancement of international law. In particular, it focuses on how international law as enunciated in the Tallinn Manual governs cyber operations in general and how it applies to cyber-unique aspects of this form of warfare. The research then reviews the achievements of the Tallinn Manual as well as its shortfalls in relation to the development of a coherent framework of international law that can be used to govern cyber operations. After this, the research turns to the increasing role of non-binding instruments of international law in the process of international law-making. The case is then made for the possibility of the Tallinn Manual being the basis on which future binding norms may be crafted to provide specific legal regulation for cyber operations.